Design of a Road Damage Complaint Application for the National Road Implementation Center I Aceh Based on Android - Adi Ahmad; Ferijal (STMIK Indonesia Banda Aceh, 2025)
The proliferation of public complaints regarding road damage has created a predicament within the community, as it has led to an increase in accidents among road users due to the prevalence of several damaged roads. The existing road damage complaint services have been suboptimal, resulting in unfulfilled complaints due to inadequate responsiveness to community submissions. In order to address this issue, it is necessary to develop an application that can effectively disseminate information about damaged roads to relevant stakeholders. This would enable prompt follow-up actions to be taken for road repairs, hence enhancing the convenience of road users. Complaints regarding national road damage are often addressed by one of the public facilities and services, specifically the Aceh National Road Implementation Center I. The concerns regarding road damage have not been effectively communicated, leading to misunderstanding regarding the appropriate recipient of the complaints. In this project, we want to develop an Android application specifically designed for submitting road damage complaints. The program will streamline the process of submitting complaints, particularly at the Aceh National Road Implementation Center I. The road damage complaint application can be designed to allow road users to submit evidence of complaints by uploading images using the android application. Users can capture photos directly from the camera or select them from the smartphone's gallery for reporting purposes.